BITE MARKS ANALYSIS USING COMPUTER ASSISTED DENTITION OVERLAY METHOD (Journal of Forensic Medicine & Toxicology, 2022)
Aim: Evaluate the computer assisted dentition overlay method for bite mark analysis. Materials and Methods: Impressions of both, maxillary as well as mandibular arches of 50 consenting volunteers were taken and dentition casts were prepared. Computer assisted overlay comparison was carried out. The findings showed that the complete dentition  Computer Assisted Dentition Overlay method dental evidence, and with the proper evaluation and presentation of the dental findings.”1 A part of Forensic Odontology deals with identification. Identification using bite mark analysis is based on the fact that each individual possess an unique dentine.2,3 Reliability of this identification has been accepted legally but controversy persists scientifically.
Keywords: Analysis; photograph; Assisted Dentition